Peran Komunikasi dalam Program Aksi Pelajar terhadap Iklim 2024 menuju Net-Zero Emissions 2050 - Sam’iyah, Sam’iyah; Ghanistyana, Lathifa Prima; Shahreza, Mirza; Isbandi, Fitri Susiswani (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Climate change has become a global issue that demands the active involvement of younger generations. In line with the 2050 Net Zero Emission target, the Central Leadership of Ikatan Pelajar Muhammadiyah (IPM), through its Environmental Affairs Division, organized the Aksi Pelajar untuk Iklim 2024 (Student Action for Climate 2024) as an effort to enhance student participation in climate change mitigation and adaptation. This study aims to analyze the implementation of the program, identify its challenges, and formulate strategic solutions to improve its effectiveness. The research employs a qualitative approach through in-depth interviews with central IPM leaders and participants, as well as observations during the kick-off event held in Kota Karang, Teluk Betung District, Bandar Lampung. The analysis refers to the Diffusion of Innovations Theory to understand how climate action ideas are disseminated among Muhammadiyah students. The findings indicate that the program effectively increases student awareness and participation and has the potential to shape agents of change in supporting the Net Zero Emission target. However, challenges remain in terms of coordination, funding, and program sustainability, which require further attention. Theoretically, this study strengthens the application of the Diffusion of Innovations Theory within the context of student-based environmental education. Practically, the findings provide recommendations for youth organizations and educational institutions in developing more inclusive, sustainable, and impactful climate action models.